Aplikasi Peserta Magang Berbasis Web pada PT. Inovasi Informatik Sinergi - Rezky Izzatul Yazidah Anwar (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
PT. Synergy Informatics Innovation faces general problems in managing the guidance of apprentices which is currently still done manually. The communication process between interns and their supervisors tends to be less efficient, resulting in disruption to the focus of supervisors and other employees. As a solution to this problem, the author plans to build a web-based information system for managing interns' guidance. This system will be created using the PHP programming language, with the Laravel framework to ensure reliability and efficiency. Choosing Tailwind CSS as a display framework aims to create an attractive and responsive interface. This system aims to facilitate communication between interns and supervisors, as well as minimize disruption to employees.